Covid-19 Pandemic and Changes in Parents’ School Preferences in Bursa Province - Sekmen, Fuat; Gökırmak, Haşmet; Demirkol, İsa (Serhat Arslan, 2022)
This study examines families’ preferences to choose the best educational institutions for their children in Bursa, Turkey, using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) Model. For this purpose, sixty-one face-to-face interviews were conducted with students and their parents at private high schools, public high schools, and open high schools in Bursa. Health concerns, quality, price, time management, safety, and self-confidence were considered the criteria in determining families’ decisions in private schools, public schools, and open high schools. The AHP results reveal that the most important criteria are health concerns with 44.91%, quality with 21.30%, safety with 12.02%, price with 8.88%, time management with 6.71%, and self-confidence is the least important criterion, which has a percentage of 6.24%. According to the criteria, values reached within the same method ranking use the criteria weights for health concerns, quality, safety, price, time management, and self-confidence. According to the AHP-weighted SAW method, private high schools are in the first place, public schools in the second place, and open high schools in the third place.
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar